Co-branded services: perceived benefits and involvement of co-branded credit cards. Issue 5 (18th June 2018) - Wang, Stephen W.; Farquhar, Jillian
Abstract : Purpose: The purpose of this paper is to further the consumer services theory in financial services marketing by examining how perceived benefits influence consumer intention-to-use a co-branded credit card and further how intention-to-use is moderated by involvement. Design/methodology/approach: A conceptual model is developed and tested. A convenience sample of users of a co-branded credit card was surveyed. The responses were analyzed using structural equation modeling. Findings: Results show a strong association between perceived benefits and co-brand equity and between co-brand equity and co-brand preference, as well as between perceived benefits and intention-to-use. The research also identifies four perceived benefits of a co-branded credit card. They also show that highly involved consumers are less affected by perceived benefits than their low involvement counterparts. Research limitations/implications: Further research might consider co-branding across categories of services and explore the ambivalent results of co-brand preference in the mode. This research is limited by the use of a convenience sample and a cross-sectional survey. A probability sample and a longitudinal element to the study would have added weight to the study's findings. Practical implications: Managers with co-branding responsibilities should focus on improving the perceived benefits of co-branded credit cards. Social implications: This study has a wider application to understanding how co-branding services may be applied in not-for-profit situations, specifically affinity card co-branding, thus generating greater revenue for charitable and social concerns. Originality/value: This research advances research in the financial services consumer theory by demonstrating a strong association between perceived benefits and intention-to-use a co-branded credit card, distinguishing between the behavioral traits of consumers with high and low levels of involvement. It thus advances the consumer theory in co-branding.